Enacting Content-Based Language Teaching in ESP Classroom for Reading Comprehension - Erwin Suhendra (Universitas Islam Negeri (UIN) Mataram, 2023)
This research aims to investigate how Content-Based Language Teaching (CBLT) was implemented and its contribution to enhancing learners' language skills in reading comprehension. The research was administered at an Indonesian private university. Drawing on the action research method. The statistical evidence showed that the mean score of the students in class A was 66.74; in class B; 64.29; in class C 65.71 and in class D 60.96 and the highest score in each category were 95 in class A; 96 in class B; 84 in class C and 90 in class D and the average score to pass the ESP course is 65. Cycle 2 was conducted from April 26th to 29th, 2023 at the same classes and schedule, and the results were; the mean score from those classes were 73.53 in class A, 73.47 in class B, 76.44 in class C, and 66.15 in class D. The research showed that there was significant satisfaction as perceived by the students regarding the implementation of CBLT for learning to read in the ESP classrooms. Future recommendations on the research related to the use of CBLT are discussed